Evaluation of Interlayer Shear Bond Devices for Asphalt Pavements - Christiane Raab; Manfred Norbert Partl; Abd El Halim Omar Abd El Halim (The Baltic Journal of Road and Bridge Engineering)
For testing the bond between asphalt pavement layers quite a variety of methods were proposed and used during the last 30 years. In many publications some of these test methods and devices were described by presenting photographs and sketches. Often photographs show the functioning of the devices only insufficiently and detailed information regarding the test devices (e.g. gap width) and test conditions (e.g. loading function, normal force) are difficult to retrieve. The following paper summarises the test methods and devices for the determination of the bond between asphalt pavement layers regarding shear testing. Direct and simple shear tests from all over the world are presented and their mode of operation shown. Furthermore, the range of applications is described and information regarding test evaluation and results are given.